2022
DOI: 10.1093/infdis/jiac148
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Alpha-Like Protein Subunit Vaccine (GBS-NN) Provides Protection in Murine Models of Group B Streptococcus Infection

Abstract: Background Group B Streptococcus (GBS) transmission during pregnancy causes preterm labor, stillbirths, fetal injury, or neonatal infections. Rates of adult infections are also rising. The GBS-NN vaccine, engineered by fusing N-terminal domains of GBS alpha C and Rib proteins, is safe in healthy, non-pregnant women, but further assessment is needed for use during pregnancy. Here, we tested GBS-NN vaccine efficacy using mouse models that recapitulate human GBS infection outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…The GBS isolates were also screened for the presence of genes encoding the alpha family proteins (Alp1, Alp2/3, Alpha C, and Rib), which are included in the protein vaccine candidate GBS-NN/NN2 ( Brokaw et al, 2022 ). A total of 527 (99%) isolates were positive for an alpha family protein gene, with majority carrying a single alpha gene only ( n = 522, 98%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GBS isolates were also screened for the presence of genes encoding the alpha family proteins (Alp1, Alp2/3, Alpha C, and Rib), which are included in the protein vaccine candidate GBS-NN/NN2 ( Brokaw et al, 2022 ). A total of 527 (99%) isolates were positive for an alpha family protein gene, with majority carrying a single alpha gene only ( n = 522, 98%).…”
Section: Resultsmentioning
confidence: 99%
“…However, implementation of a CPS-based vaccine against carriage of GBS during pregnancy has the potential to exert selective pressure on GBS population, which might lead to serotype switching, serotype replacement and expansion of non-vaccine GBS types ( Gladstone et al, 2015 ). Alternative protein-based vaccine formulations are also under development, which includes a vaccine based on the N-terminal domains of four GBS surface proteins from the alpha protein family (Alpha C, Alp1, Alp2/3, and Rib; Brokaw et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…injection of 0.5 mL), and minipigs for the cardiovascular study. This primary species selection was based upon earlier nonclinical pharmacodynamic studies in rodents that demonstrated that GBS‐NN induced an immune response in mice, which was found to be protective in the offspring of immunized female mice (Brokaw et al, 2022; Stålhammar‐Carlemalm et al, 2007; Minervax ApS, MNV001, MNV002, MNV004, MNV007, MNV008, MVX‐NC‐006, unpublished internal company reports). This was confirmed in the repeat‐dose rat studies as all of the animals immunized with GBS‐NN or GBS‐NN2 antigens showed antigen‐specific responses.…”
Section: Discussionmentioning
confidence: 99%
“…The initial vaccine candidate, GBS‐NN, was based on the N‐terminal domains of Rib and AlphaC surface proteins and preclinical repeat dose and local tolerance studies were performed accordingly. However, assessments of the functionality of IgG antibodies generated during a subsequent Phase I clinical study identified that the degree of cross‐reactivity with the two other N‐terminal proteins Alp1 and Alp2/3 was not as robust as would be required for a GBS protein vaccine to be effective (Brokaw et al, 2022; Fischer et al, 2021). Therefore, MinervaX modified the vaccine candidate to include all four relevant N‐terminal proteins, and designated it GBS‐NN/NN2.…”
Section: Introductionmentioning
confidence: 99%
“…Research on GBS prevention in murine models through a recombinant alpha-like protein subunit vaccine been effective, as vaccinated mice had IgG titers versus controls, and specifically, though vaccination did not eliminate GBS during ascending infection in pregnancy, vaccinated mice experienced fewer in utero fetal deaths [175]. The current global position on GBS vaccines is at a Phase II trial level.…”
Section: Prevention Treatmentmentioning
confidence: 99%